Transcriptomic HIV-1 reservoir profiling reveals a role for mitochondrial functionality in HIV-1 latency. - Shirley Man; Jade Jansen; Stefanie Kroeze; Teunis B H Geijtenbeek; Neeltje A Kootstra (PLoS Pathogens)
Identifying cellular and molecular mechanisms maintaining HIV-1 latency in the viral reservoir is crucial for devising effective cure strategies. Here we developed an innovative flow cytometry-fluorescent in situ hybridization (flow-FISH) approach for direct ex vivo reservoir detection without the need for reactivation using a combination of probes detecting abortive and elongated HIV-1 transcripts. Our flow-FISH assay distinguished between HIV-1-infected CD4+ T cells expressing abortive or elongated HIV-1 transcripts in PBMC from untreated and ART-treated PWH from the Amsterdam Cohort Studies. This flow-FISH method was employed to isolate CD4+ T cells expressing abortive or elongated HIV-1 transcripts from five ART-naïve PWH for transcriptomic analysis by 3' RNA sequencing. Supervised cluster analysis identified several differentially expressed mitochondrial genes in infected CD4+ T cells with abortive HIV-1 transcripts compared to cells containing elongated HIV-1 transcripts. Notably, enhancing mitochondrial function induced HIV-1 transcription in PBMC from PWH. Our data strongly suggests that cellular metabolism is involved in maintaining HIV-1 latency and show that improving mitochondrial functions induces HIV-1 transcriptional activity in PWH. These findings underline the relevance of metabolic regulation in HIV-1 infection, and support the development of strategies modulating immunometabolism to target viral latency.